Saberes tradicionais Krahô: contribuições para Educação Física indígena bilíngue e intercultural - Leite, Francinaldo Freitas (2018)
The Krahô indigenous people occupy a territory of the northeast region of the state of Tocantins. Part of the immaterial patrimony of the Krahô includes traditional knowledge rooted in the ludic universe and its corporeality, which is revealed in their rites, dances, myths and their cosmology. The overall objective of this dissertation is to propose a pedagogical approach for the teaching of Physical Education in the Krahô indigenous school context that is appropriate for the school’s intercultural and bilingual curriculum. This study is classified methodologically as ethnographically based. Ethnographic research is characterized by the objective of describing and interpreting the relations among a determined group of people within their cultural context. Several key figures participated in the study as research assistants, including teachers at the state indigenous school 19 de Abril, indigenous leaders and members of the Manoel Alves Pequeno village community, located in the Kraholândia indigenous territory. For the theoretical basis, Melatti (1978, 2007, 2009a, 2009b), Geertz (1989, 2002), Daolio (1995, 2004, 2007), and Albuquerque (2012, 2014) were used as primary authors, in addition to the RCNEI (1998) and SEDUC (2013) as curricular references. For the development of the methodology, data collection was conducted through participant observation, open interviews and documentary analysis. According to the results, we find that indigenous education presents itself as a strategy for strengthening the culture of the Krahô, in order to foster intercultural dialogue between this indigenous group and other ethnic groups. In a similar sense, indigenous Physical Education can play a role in the Krahô indigenous context, based on an approach that contemplates the ludic element, culture and corporeality, and can also contribute to the maintenance, preservation and rescue of Krahô traditional knowledge. We find that Krahô Indigenous Physical Education, within an intercultural and bilingual perspective, should include corporeal cultures of movement of the world, Brazil, other indigenous peoples, as well as the Krahô people’s own corporeal culture of movement as pedagogical content. Therefore, the realization of the Traditional Krahô Games as a practice of the group’s corporeal culture of movement can be integrated as a subject to be studied in the village school context.